Overall survival after pelvic exenteration for gynecologic malignancy - Westin, Shannon N. (2014)
BACKGROUND: 5-year survival after pelvic exenteration for gynecologic malignancies has been reported as high as 60%. The objective of this study was to determine overall survival (OS) after pelvic exenteration and evaluate factors impacting outcome. METHODS: A retrospective review of all women who underwent pelvic exenteration at our institution between February 1993 and December 2010 was performed. OS was defined as time from exenteration to date of death or last contact. Survival analysis was performed using the Kaplan Meyer method. Multivariate analysis was performed to determine the impact of clinical and pathologic factors on survival outcomes. RESULTS: One hundred sixty patients with gynecologic malignancy underwent pelvic exenteration. Five-year recurrence free survival (RFS) was 33% (95%CI 0.25 – 0.40). Factors which negatively impacted RFS included shorter treatment-free interval (p=.050), vulvar primary (p=.032), positive margins (p<.001), lymphovascular space invasion (LVSI, p<.001), positive lymph nodes (p<.001) and perineural invasion (p=0.030). In multivariate analysis, positive margins (p=.040), positive nodes (p<.001) and lymphovascular space invasion (LVSI, p=.003) retained a significant impact on RFS. Five-year OS was 40% (95% CI 0.32 – 0.48). Factors which negatively impacted OS included vulvar primary (p=.04), positive margins (p<.001), LVSI (p<.001), positive lymph nodes (p<.001) and perineural invasion (p=.008). In multivariate analysis, positive nodes (p=.001) and LVSI (p=.001) retained a significant impact on OS. CONCLUSION: Five-year OS after pelvic exenteration was 40%. Survival outcomes have not significantly improved despite improvements in technique and patient selection. Multiple non-modifiable factors at the time of exenteration are associated with poor survival.